2013
DOI: 10.1177/1541931213571278
|View full text |Cite
|
Sign up to set email alerts
|

Visual, Tactile, and Bimodal Presentation of Lateral Drift in Simulated Helicopter

Abstract: Helicopter landing and take-off in degraded visibility caused by blowing sand or dust (brown-out) may distort the pilot's comprehension of the helicopter's position. This is a serious problem that may lead to unattended lateral drift or descending rate. We have previously shown advantages of redundant tactile and multimodal information a simulated combat vehicle. In order to investigate if lateral drift in a helicopter can be reduced by use of a drift display an experiment with a simulated helicopter was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…That performance with the best tactile drift display configurations (basic with slow onset rate and complex with static onset rate) was equal to the already validated visual display supports the possibilities of using a tactile display. This also confirms results from our previous research that has shown that lateral drift, in principal, can be controlled equally well with both visual and tactile drift displays [11].…”
Section: Discussionsupporting
confidence: 91%
“…That performance with the best tactile drift display configurations (basic with slow onset rate and complex with static onset rate) was equal to the already validated visual display supports the possibilities of using a tactile display. This also confirms results from our previous research that has shown that lateral drift, in principal, can be controlled equally well with both visual and tactile drift displays [11].…”
Section: Discussionsupporting
confidence: 91%
“…Our evaluation also pointed towards many possible improvements. An interesting venue for development is how to prototype patterns of vibrations that move across multiple engines, as for example in a haptic vest (Oskarsson, Lif, Hedström, Andersson, Lindahl & Tullberg, 2013;Prasad, Teale, Goldberg, Hammond, 2014;Prasad, Teale, Olubeko, Hammond, 2014). How to prototype other forms of haptic feedback (e.g.…”
Section: Future Researchmentioning
confidence: 99%
“…The location of a vibration on the body can also be used to express different meanings. That is, a signal on the left shoulder could represent something else than a signal on the right shoulder (Oskarsson, Lif, Hedström, Andersson, Lindahl & Tullberg, 2013;Prasad, Teale, Goldberg, Hammond, 2014;Prasad, Teale, Olubeko, Hammond, 2014). A tactile vest with several vibrotactile actuators allow for spatiotemporal patterns, such as a vibration that moves down the users back or from left to right.…”
Section: Introductionmentioning
confidence: 99%